Performance Evaluation and Degradation Mechanism for Proton Exchange Membrane Fuel Cell with Dual Exhaust Gas Recirculation - Yang Liu; Zhengkai Tu; Siew Hwa Chan (Advanced Energy & Sustainability Research, 2023)
Fuel gas utilization and water management are particularly challenging integrated engineering problems in hydrogen–oxygen proton exchange membrane fuel cell (H2/O2 PEMFC) systems. Herein, a standardized process is adopted to evaluate the performance and investigate the degradation mechanisms of a PEMFC with dual exhaust gas recirculation. The purpose of incorporating recirculation subsystems in the fuel cell is to achieve a high fuel gas utilization rate and realize effective water management inside the stack, which consists of 3D‐printed ejectors and a customized recirculation pump. Evaluation of the electrochemical performance degradation and morphological characterization of the fuel cells under different operating strategies are performed after 50 h durability experiments. At a current density of 400 mA cm−2, the performance degradation rates of the stack decrease from 16.50% to 7.49% and 0.71% in the ejector and recirculation pump operation strategies, respectively. The results show that using exhaust gas recirculation devices (ejector/pump) in the fuel cell stack can help in effectively mitigating water flooding and chemical degradation of the membrane electrode assembly. The findings of the study provide a perspective on the exhaust gas recirculation behavior and contribute to the engineering application of H2/O2 PEMFCs.